Longitudinal Brain Atrophy Rates in Transient Ischemic Attack and Minor Ischemic Stroke Patients and Cognitive Profiles - Munir, Muhammad; Ursenbach, Jake; Reid, Meaghan; Gupta Sah, Rani; Wang, Meng; Sitaram, Amith; Aftab, Arooj; Tariq, Sana; Zamboni, Giovanna; Griffanti, Ludovica; Smith, Eric E.; Frayne, Richard; et al. (Frontiers in Neurology, 2019)
Introduction: Patients with transient ischemic attack (TIA) and minor stroke demonstrate cognitive impairment, and a four-fold risk of late-life dementia. Aim: To study the extent to which the rates of brain volume loss in TIA patients differ from healthy controls and how they are correlated with cognitive impairment. Methods: TIA or minor stroke patients were tested with a neuropsychological battery and underwent T1 weighted volumetric magnetic resonance imaging scans at fixed intervals over a 3-year period. Linear mixed effects regression models were used to compare brain atrophy rates between groups, and to determine the relationship between atrophy rates and cognitive function in TIA and minor stroke patients. Results: Whole brain atrophy rates were calculated for the TIA and minor stroke patients; n=38 between 24 hours and 18 months, and n=68 participants between 18 and 36 months, and were compared to healthy controls. TIA and minor stroke patients demonstrated a significantly higher whole brain atrophy rate than healthy controls over a 3-year interval (p=.015). Older age (p=0.003), later time interval i.e. 2nd intervals (p=0.007), and diabetes (p=0.001) independently predicted higher atrophy rate across groups. Among TIA and minor stroke patients, higher brain annualized atrophy rate over the first 18-month interval were associated with poorer verbal memory (p=0.032), while the second interval atrophy rate was associated with reduced information processing speed (p=0.047). Conclusion: TIA and minor stroke patients experience a significantly higher rate of whole brain atrophy. Additional studies are needed to determine what disease processes are associated with early brain atrophy.